Synthesis and initial in vitro evaluations of novel antioxidant aroylhydrazone iron chelators with increased stability against plasma hydrolysis - Hruskova, Katerina; Kovarikova, Petra; Bendova, Petra; Haskova, Pavlina; Mackova, Eliska; Stariat, Jan; Vavrova, Anna; Vavrova, Katerina; Simunek, Tomas (Chemical research in toxicology, 2011)
Oxidative stress is known to contribute to a number of cardiovascular pathologies. Free intracellular iron ions participate in the Fenton reaction and therefore substantially contribute to the formation of highly toxic hydroxyl radicals and cellular injury. Earlier work on the intracellular iron chelator salicylaldehyde isonicotinoyl hydrazone (SIH) has demonstrated its considerable promise as an agent to protect the heart against oxidative injury both in vitro and in vivo. However, the major limitation of SIH is represented by its labile hydrazone bond that makes it prone to plasma hydrolysis. Hence, in order to improve the hydrazone bond stability, nine compounds were prepared by a substitution of salicylaldehyde by the respective methyl- and ethylketone with various electron donors or acceptors in the phenyl ring. All the synthesized aroylhydrazones displayed significant iron-chelating activities and eight chelators showed significantly higher stability in rabbit plasma than SIH. Furthermore, some of these chelators were observed to possess higher cytoprotective activities against oxidative injury and/or lower toxicity as compared to SIH. The results of the present study therefore indicate the possible applicability of several of these novel agents in the prevention and/or treatment of cardiovascular disorders with a known (or presumed) role of oxidative stress. In particular, the methylketone HAPI and nitro group-containing NHAPI merit further in vivo investigations.
Keywords: Oxidative Stress; Hydrolysis; chelátory železa; oxidační stres; Drug Stability; hydrolýza; Iron Chelating Agents; hydrazony; krysa rodu Rattus; Antioxidants; zvířata; buněčné linie; antioxidancia; Cell Line; hydroxylový radikál; Hydrazones; Hydroxyl Radical; králíci; Rats; stabilita léku; aldehydy; Animals; Aldehydes; Rabbits